A novel seven-coordinate adduct of cadmium(II) in an N3S3 macrocycle environment - Ismail, A.R.; Bin Silong, Sidik; Skelton, Brian W.; White, Allan H. (CSIRO Publishing, 2003)
The structural characterization of the 1:1 adduct of the ligand with cadmium (II) bromide was presented. The asymmetric unit of this structure carries two ligands in examples of the novel seven-coordinate [BrCdL]+ species. The results of the single-crystal x-ray structure determination were consistent with formulation of the present complex as a 1:2 L/CdBr2 adduct.